Association between tuberculosis and bronchial asthma - Garg, Kranti; Karahyla, Jai Kishan (International Journal of Research in Medical Sciences, 2017)
Background: Everything that wheezes is not asthma. In patients of tuberculosis (TB), wheezing can be because of bronchial asthma, or many other causes. Asthma and other causes of wheezing need to be differentiated, as the treatment should be planned accordingly. Methods: Patients of active/quiescent tuberculosis who presented to Department of Tuberculosis and Chest Diseases, Government Medical College, Patiala, Punjab, India, with complaints of breathlessness and had rhonchi on examination were subjected to bronchodilator reversibility testing to prove if they were suffering from concomitant asthma. Patients thus found to have tuberculosis along with asthma were analyzed with respect to age, sex, rural urban differences and timing of diagnosis of either disease. Patients who developed asthma after tuberculosis were further analyzed for duration between completion of anti-tubercular treatment (ATT) and onset of asthma, family history of asthma and correlation of radiological manifestations and lung function measurements. Aim was to find association, if any, between tuberculosis and asthma. Results: Over 6 months, 69 patients of tuberculosis along with asthma were found. Only 21/69 (30.4%) patients developed tuberculosis after asthma. 48/69 (69.6%) patients developed asthma after tuberculosis. Majority (25/48=52.1%) of them developed asthma within 5 years of completion of ATT (p=0.020). Only 2/48 (2.9%) patients had a positive family history for asthma. Lung function abnormalities correlated with the extent of radiological involvement in these patients who developed asthma after tuberculosis (p ≤0.0001). Conclusions: Patients of active/quiescent tuberculosis who present with breathlessness and have rhonchi on examination should be treated for asthma only after confirmation of the diagnosis, as there can be other reasons for the same.